Como Alcançar Bom Desempenho Durante uma Prova Didática em Concursos Públicos para Professor Universitário - Carlos Frederico Duarte Rocha (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2011)
In this essay I present a set of suggestions and procedures to be considered in the preparation of a class by candidates during a didactic test to a University teacher position in public contests. These points, if considered when preparing the lecture, can substantially improve their performance in a public contest. The set of points presented and analyzed, if carefully considered, can significantly increase the chance of a consistent class for its content, can promote an interesting way of approaching, be attractive in its aesthetic, gaining in clarity, understanding and quality of information transmission, potentially leading the candidate University teacher to be better evaluated in its class.